Counseling Tobacco Smoke Exposure Reduction Measures in Pediatrics: A Quality Improvement Project. Issue 5 (15th September 2022) - Ferguson, Kevin; Krishnan, Sankaran; Sullivan, Emily; Bhela, Shyall; Dozor, Allen J.; Welter, John J.
Abstract : Introduction: With over 40% of children in the USA exposed to tobacco smoke, the AAP recommends tobacco smoke exposure (TSE) assessment during clinic visits. We aimed to increase the rates of TSE screening and provider counseling regarding TSE reduction using an evidence-based approach. Methods: We conducted the project at a large pediatric pulmonology practice. Baseline caregiver surveys and medical record review of TSE documentation took place in July/August, 2019. From September 2019 to July 2021, PDSA cycles were conducted to increase TSE screening and reduce counseling. Results: Before starting the project, 18% of smoking caregivers acknowledged smoking in the home and 41% in the car. While caregivers strongly desired to decrease TSE (median 9.4/10 on Likert scale), physician counseling of TSE reduction was offered only to 44%. PDSA cycles led to refining our patient passport, a document used during patient intake, which increased screening of TSE from 46% to 85%. Creating an educational handout in our electronic record addressing TSE increased TSE reduction counseling from 44% to 80% of children with smokers in the home. Conclusions: Incorporating TSE screening into established nursing documentation of vital signs led to the sustained screening of TSE among children in a pediatric pulmonology practice. Embedding educational material in our electronic record and changes in clinic processes increased TSE reduction counseling. Similar changes could improve rates of counseling caregivers of other guidelines aimed to improve the children's health.